The Implications of Using Estimated Solar Radiation on the Derivation of Potential Evapotranspiration and Soil Moisture Deficit within an Embankment. (2016) - Helm, Peter; Stirling, Ross; Glendinning, Stephanie
Abstract: In the absence of measured data, evapotranspiration is commonly estimated at a given site according to the methods outlined by Allen et al. (1998). Their work provides a system of calculation to derive the solar radiation values required to predict the available energy for water vaporisation. As such estimations of evapotranspiration are very dependent on the available data. In this work, meteorological parameters including air temperature, relative humidity, wind speed, near-surface soil temperature, shortwave and net solar radiation were measured for a complete year at the BIONICS trial embankment, Newcastle, UK. Estimates were made of the net radiation for a number of cases (1. no radiation data and 2. measured incident short wave radiation) and compared to the field monitored values. These data were in turn used to estimate the potential evapotranspiration ( ET p ) from the embankment. The results indicate that the net radiation and hence ET p derived entirely from estimated data are significantly higher than those derived with measured shortwave or net radiation. Results for estimates of ET p derived from monitored shortwave and net radiation data are a close match to each other. In order to investigate the potential effects on slope stability, an assessment of soil moisture deficit was undertaken. The results indicate that numerical models using the varying estimates of ET p would likely produce different results in terms of generated suctions and suction dissipation and so undergo different magnitudes of shrink-swell cycling, in turn leading to varying rates of strain softening behaviour, differing calculated factors of safety and differing modelled time to failure.